Activation of the ACE2/Angiotensin-(1–7)/Mas Receptor Axis Enhances the Reparative Function of Dysfunctional Diabetic Endothelial Progenitors - Jarajapu, Yagna P.R. (American Diabetes Association, 2013)
We tested the hypothesis that activation of the protective arm of the renin angiotensin system, the angiotensin-converting enzyme 2 (ACE2)/angiotensin-(1-7) [Ang-(1-7)]/Mas receptor axis, corrects the vasoreparative dysfunction typically seen in the CD34(+) cells isolated from diabetic individuals. Peripheral blood CD34(+) cells from patients with diabetes were compared with those of nondiabetic controls. Ang-(1-7) restored impaired migration and nitric oxide bioavailability/cGMP in response to stromal cell–derived factor and resulted in a decrease in NADPH oxidase activity. The survival and proliferation of CD34(+) cells from diabetic individuals were enhanced by Ang-(1-7) in a Mas/phosphatidylinositol 3-kinase (PI3K)/Akt-dependent manner. ACE2 expression was lower, and ACE2 activators xanthenone and diminazine aceturate were less effective in inducing the migration in cells from patients with diabetes compared with controls. Ang-(1-7) overexpression by lentiviral gene modification restored both the in vitro vasoreparative functions of diabetic cells and the in vivo homing efficiency to areas of ischemia. A cohort of patients who remained free of microvascular complications despite having a history of longstanding inadequate glycemic control had higher expression of ACE2/Mas mRNA than patients with diabetes with microvascular complications matched for age, sex, and glycemic control. Thus, ACE2/Ang-(1-7)\Mas pathway activation corrects existing diabetes-induced CD34(+) cell dysfunction and also confers protection from development of this dysfunction.